Human Capital Management as A Catalyst for Organizational Change: A Study on West Java Health Laboratory (BLUD) Transition - Supriarti, Ria Andiani; Febriansyah, Hary (Yayasan Sinergi Kawula Muda, 2025)
Human capital management is limited to administrative tasks despite their importance to an organization's performance. This study seeks strategic human capital management (HCM) methods to help BLUD mplementation succeed, focusing on flexible government norms. The study uses qualitative thematic analysis and quantitative SEM-PLS to assess the organization's human capital practices. The results reveal that leadership techniques are good, but other areas for change can be improved. The paper recommends an dvanced Human Capital Management System (HCMS) for leadership development, learning, workforce efficiency, knowledge accessibility, and employee engagement. A structured HCMS can incorporate these improvements to manage and expand human capital and align employee competencies with BLUD transition goals. The research recommends 7S change management for HCM implementation. The framework helps the organization recognize change and handle critical challenges in line with transformation goals. The need for a specialist committee to oversee the development and implementation of these initiatives emphasizes leadership's role in organizational transformation. According to the study, digitalization, talent management, systematic training, employee well-being, continuous competency, and performance evaluation are critical to long-term success. This study suggests ways an organization can improve its human capital management to move to BLUD status smoothly. To validate and improve the HCM strategy, future studies should apply.